Assessing the impact of the COVID-19 pandemic and formulating policy responses to protect vulnerable sectors and populations in Rwanda - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Using PIM economic policy modelling tools, IFPRI provided strategic and timely advice to the Government of Rwanda to assess the impact of the COVID-19 pandemic and of the measures taken to control its spread, implement short-term policy responses to protect vulnerable sectors and populations and formulate longer-term policies to spur economic recovery.